Range expansion and population increase of the Gadwall in eastern North America - Henny, Charles J; Holgersen, Norman E (Wildfowl, 1974)
A disjunct breeding population of Gadwall in eastern North America was first recorded in 1939. This population has extended its range during recent years to the point where it is now found breeding in more than thirty locations (primarily National Wildlife Refuges and Wildlife Management Areas). These are 1,600-2,000 km (1,000-1,200 miles) from the main breeding range in the west and midwest. The number of breeding birds and the harvest have both increased during the last decade. Approximately 40,000 Gadwall were harvested in the northern portion of the Atlantic Flyway between 1961 and 1970. The impoundment of water seems to be responsible for the increase, providing focal points for nesting activities.